2017
DOI: 10.1103/physreva.96.042326
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Einstein-Podolsky-Rosen steering of continuous-variable bipartite states by non-Gaussian pseudospin measurements

Abstract: Einstein-Podolsky-Rosen (EPR) steering is an asymmetric form of correlations which is intermediate between quantum entanglement and Bell nonlocality, and can be exploited as a resource for quantum communication with one untrusted party. In particular, steering of continuous-variable Gaussian states has been extensively studied theoretically and experimentally, as a fundamental manifestation of the EPR paradox. While most of these studies focused on quadrature measurements for steering detection, two recent wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…In panel (a) we show how Reid's criterion fails to witness any quantum steering in this case. In panel (b) we witness steering through In panel (a) we show the observations arising from the application of Reid's criterion S hom R (A) (28). The legend is the same as in panel (b).…”
Section: Purely Non-gaussian Quantum Steeringmentioning
confidence: 93%
See 2 more Smart Citations
“…In panel (a) we show how Reid's criterion fails to witness any quantum steering in this case. In panel (b) we witness steering through In panel (a) we show the observations arising from the application of Reid's criterion S hom R (A) (28). The legend is the same as in panel (b).…”
Section: Purely Non-gaussian Quantum Steeringmentioning
confidence: 93%
“…5 we show the steering witness, as measured in the two directions. In panel (a) we use Reid's criterion (28), which leads to strongly asymmetric results, as no EPR steering from the mode where the photon was subtracted is observed. Yet, remarkably, in panel (b) the vio-lation of the metrological inequality, not only witnesses steering from the photon subtracted mode, but actually leads to a larger value for the steering witness.…”
Section: B Quantum Steering After Local Photon Subtractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works also revealed that there exist Gaussian states which are only steerable by suitable non-GPOVMs. In [ 25 ], the authors considered pseudospin measurements instead of GPOVMs for any two-mode Gaussian states and found that these observables are always less sensitive than conventional Gaussian observables for steering detection. Note that GPOVMs are accessible in laboratory by means of homodyne detections and Gaussian transformations.…”
Section: Definition and Criterion Of Gaussian Quantum Epr Steeringmentioning
confidence: 99%
“…Wittmann et al in [ 23 ] gave EPR steering inequalities with three Pauli measurements; and then, as a generalization of the Pauli matrices, Marciniak et al in [ 24 ] found EPR steering inequalities with mutually unbiased bases. For continuous-variable systems, the authors in [ 25 ] performed a systematic investigation of EPR steering for bipartite Gaussian states by pseudospin measurements. Kogias and Adesso [ 26 ] gave a measure of EPR steering for two-mode continuous variable states.…”
Section: Introductionmentioning
confidence: 99%